1994
DOI: 10.1161/01.str.25.9.1847
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin contributes to microvascular obstructions and parenchymal changes during early focal cerebral ischemia and reperfusion.

Abstract: Background and Purpose Ischemic cerebral injury is associated with activation of the blood coagulation cascade. To elucidate the contribution of fibrin formation to microvascular injury during focal cerebral ischemia and reperfusion, we have studied the time course and the localization of fibrin deposition in cerebral microvessels and the surrounding tissues during ischemia/reperfusion in a well-described nonhuman primate model.Methods Cerebral tissues from adolescent male baboons were examined after 2-hour mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(155 citation statements)
references
References 33 publications
4
146
1
3
Order By: Relevance
“…Earlier animal studies have shown that 'no reflow' within the microvascular compartment is an important condition after MCA occlusion that promotes infarct development (Dawson et al, 1997;Okada et al, 1994). Okada et al showed that local formation of fibrin contributes to microvascular obstruction (Okada et al, 1994), which may explain thepartial-treatment effect we found after administration of rt-PA. Further improvement of this effect by microbubble-enhanced ultrasound is in line with experimental data showing that the efficacy of rt-PA on fibrin-rich clots can be enhanced in combination with ultrasound (Saguchi et al, 2008).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Earlier animal studies have shown that 'no reflow' within the microvascular compartment is an important condition after MCA occlusion that promotes infarct development (Dawson et al, 1997;Okada et al, 1994). Okada et al showed that local formation of fibrin contributes to microvascular obstruction (Okada et al, 1994), which may explain thepartial-treatment effect we found after administration of rt-PA. Further improvement of this effect by microbubble-enhanced ultrasound is in line with experimental data showing that the efficacy of rt-PA on fibrin-rich clots can be enhanced in combination with ultrasound (Saguchi et al, 2008).…”
Section: Discussionmentioning
confidence: 68%
“…Okada et al showed that local formation of fibrin contributes to microvascular obstruction (Okada et al, 1994), which may explain thepartial-treatment effect we found after administration of rt-PA. Further improvement of this effect by microbubble-enhanced ultrasound is in line with experimental data showing that the efficacy of rt-PA on fibrin-rich clots can be enhanced in combination with ultrasound (Saguchi et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Several small arterioles, venules, and capillaries contained intraluminal fibrin deposits ( Figure 3A) of grade 1 on the scale for fibrin localization in an MCA model. 25 Extravascular deposition of fibrin grade 2 was also found, suggesting breakdown of the bloodbrain barrier ( Figure 3A). Figure 3B shows several capillaries in the ischemic hemisphere positive for fibrin, in contrast to insignificant fibrin staining in a matched region of the contralateral hemisphere ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Tissue fixed in 10% buffer formalin was processed, and 7-m-thick, paraffin coronal sections from each block were cut and stained. Fibrin was localized using a grading scale 25 : 1, fibrin deposition limited to intravascular space; 2, fibrin deposition in the intravascular lumen and the perivascular space; and 3, fibrin lattices in the extravascular or parenchymal tissue only. For immunostaining, anti-mouse fibrin II antibody (NYB-T2G1, Accurate Chemical Science Corp) 26 (1:1000 dilution) was used.…”
Section: Histopathologymentioning
confidence: 99%